Pengaruh Konten Media Sosial, Influencer, Dan Ulasan Online Terhadap Keputusan Pembelian Produk Fashion Pada Marketplace (Studi Pada Kalangan Generasi Z Di Kota Malang ) - Eka Lailatul Rohma; Nurhajati Nurhajati; Harun Alrasyid (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research aimed to examine and explain the influence of content presented through social media, the role of influencers, and online reviews on the purchasing decision-making process of fashion products in marketplaces among Generation Z in Malang City. The data obtained were then analyzed using multiple linear regression. Prior to the main analysis, instrument and research model testing was conducted, including validity, reliability, and classical assumption testing to ensure the validity of the data used in the analysis. The results showed that social media content, influencers, and online reviews collectively have a significant influence on purchasing decisions for fashion products in marketplaces. Meanwhile, the remaining 15.4% is influenced by factors outside the variables analyzed in this study. The findings of this study illustrate that a digital marketing strategy that optimally utilizes social media, supported by the credibility of influencers and the quality of informative and convincing online reviews, plays a crucial role in driving purchasing decisions for fashion products in the marketplace, particularly among Generation Z consumers. Keywords: Social Media Content, Influencers, Online Reviews, Purchasing Decisions.